Μ-Opioid Receptor Activation Directly Modulates Intrinsically Photosensitive Retinal Ganglion Cells. (1st June 2019) - Cleymaet, Allison M.; Gallagher, Shannon K.; Tooker, Ryan E.; Lipin, Mikhail Y.; Renna, Jordan M.; Sodhi, Puneet; Berg, Daniel; Hartwick, Andrew T.E.; Berson, David M.; Vigh, Jozsef
Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) encode light intensity and trigger reflexive responses to changes in environmental illumination. In addition to functioning as photoreceptors, ipRGCs are post-synaptic neurons in the inner retina, and there is increasing evidence that their output can be influenced by retinal neuromodulators. Here we show that opioids can modulate light-evoked ipRGC signaling, and we demonstrate that the M1, M2 and M3 types of ipRGCs are immunoreactive for μ-opioid receptors (MORs) in both mouse and rat. In the rat retina, application of the MOR-selective agonist DAMGO attenuated light-evoked firing ipRGCs in a dose-dependent manner (IC50  < 40 nM), and this effect was reversed or prevented by co-application of the MOR-selective antagonists CTOP or CTAP. Recordings from solitary ipRGCs, enzymatically dissociated from retinas obtained from melanopsin-driven fluorescent reporter mice, confirmed that DAMGO exerts its effect directly through MORs expressed by ipRGCs. Reduced ipRGC excitability occurred via modulation of voltage-gated potassium and calcium currents. These findings suggest a potential new role for endogenous opioids in the mammalian retina and identify a novel site of action—MORs on ipRGCs—through which opioids might exert effects on reflexive responses to environmental light. Highlights: In the rodent retina M1-M3 types of intrinsically photosensitive ganglion cells (ipRGCs) express μ-opioid receptors (MORs). Light-evoked firing of ipRGCs is attenuated by the MOR-specific agonist DAMGO in a dose-dependent manner. MOR activation reduces ipRGC excitability by modulating IK and reducing the amplitude of non-inactivating ICa . These findings suggest a potential new role for endogenous opioids in the mammalian retina.